2018
DOI: 10.1021/acs.jpclett.8b00575
|View full text |Cite
|
Sign up to set email alerts
|

HOMO Level Pinning in Molecular Junctions: Joint Theoretical and Experimental Evidence

Abstract: A central issue in molecular electronics in order to build functional devices is to assess whether changes in the electronic structure of isolated compounds by chemical derivatization are retained once the molecules are inserted into molecular junctions. Recent theoretical studies have suggested that this is not always the case due to the occurrence of pinning effects making the alignment of the transporting levels insensitive to the changes in the electronic structure of the isolated systems. We explore here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 75 publications
2
71
0
Order By: Relevance
“…Recent noteworthy works have described that the analytic single-level model (SLM) or Newns-Anderson Model, basically derived from the Landauer transport theory, can be employed to extract the effective energy offset (e.g., ε h = |E F − E HOMO | for p-type transport and ε l = |E F − E LUMO | for n-type transport) and the contact coupling Γ between molecules and electrodes from I-V characteristics of the junctions [34,[51][52][53][54][55]. The excellent fits of the SLM to I-V curves have shown its validity to examine coherent, non-resonant tunneling transport that is typical of a great part of both aromatic and aliphatic junctions.…”
Section: Single-level Model Analysismentioning
confidence: 99%
“…Recent noteworthy works have described that the analytic single-level model (SLM) or Newns-Anderson Model, basically derived from the Landauer transport theory, can be employed to extract the effective energy offset (e.g., ε h = |E F − E HOMO | for p-type transport and ε l = |E F − E LUMO | for n-type transport) and the contact coupling Γ between molecules and electrodes from I-V characteristics of the junctions [34,[51][52][53][54][55]. The excellent fits of the SLM to I-V curves have shown its validity to examine coherent, non-resonant tunneling transport that is typical of a great part of both aromatic and aliphatic junctions.…”
Section: Single-level Model Analysismentioning
confidence: 99%
“…However, we did not observe this trend in our experiments, suggesting that the influence of nitro side-groups on single-molecule conductance is much more complicated than expected. Recently, Rodriguez-Gonzalez et al found that the electron-withdrawing groups, such as fluorine side-groups and nitro side-groups, change the orbital of the isolated dithiolated oligophenylene ethynylene molecule (S-OPE) [ 39 ], but hardly change the energy gap between Fermi level and the HOMO level of molecule in the junction due to pinning effects [ 40 , 41 ]. They ascribed that the variety of the conductance value caused by the side group might arise from the molecule-electrode interfacial coupling in S-OPE system rather than the electron-withdrawing nature of side groups [ 39 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Rodriguez-Gonzalez et al found that the electron-withdrawing groups, such as fluorine side-groups and nitro side-groups, change the orbital of the isolated dithiolated oligophenylene ethynylene molecule (S-OPE) [ 39 ], but hardly change the energy gap between Fermi level and the HOMO level of molecule in the junction due to pinning effects [ 40 , 41 ]. They ascribed that the variety of the conductance value caused by the side group might arise from the molecule-electrode interfacial coupling in S-OPE system rather than the electron-withdrawing nature of side groups [ 39 , 41 ]. We believed that, apart from the electron withdrawing effect of the nitro group, the addition of the nitro side-group might also alter the interfacial coupling of pyridine and Au electrodes, thereby causing the unexpected change of single-molecule conductance.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence of such a pinning has also been provided in recent studies. 48,49 Further, the evolution of resonance peaks arising from LUMO (shown in Fig. 3 Further, the transmission spectra of para and meta connected acenes reveals that the position of resonance peaks which correspond to the conduction channel through molecular orbitals is identical for both para and meta connections.…”
Section: Qi In Parent Non-magnetic Acenesmentioning
confidence: 91%